Pengaruh Pengetahuan Multimedia Pembelajaran, Berpifikir Kritis terhadap Efektifitas Modul E-Learning Mahasiswa Fakultas Teknik UNM - Latif, Nurlaela; Romadin, Achmad; Hasyim, Muhammad (Universitas Mataram, 2024)
This study is an Ex Post Facto study because the independent variables are not manipulated or subjected to specific treatments; instead, they are analyzed based on symptoms that appeared in respondents before the study's initiation. Adopting a cause-and-effect approach of